Regime-Dependent Environmental Tax Multipliers : Evidence from 75 Countries - Schoder, Christian (World Bank, Washington, DC, 2021)
This paper reviews the main transmission channels of an environmental tax reform shifting the tax burden from labor to carbon emission. The analysis uses a simple open-economy macro model and estimates dynamic environmental tax as well as personal income tax multiplier effects on output and employment for a panel of 75 highand low-income countries from 1994 to 2018. Tax policy changes are identified by cyclically adjusting the tax revenues. The estimated environmental tax multiplier effects on output range from 1 on impact to 1.8 at the peak. Personal income tax multipliers are slightly higher, ranging from 1.4 to 2.3. While income taxes reduce employment, environmental taxes do not. Environmental tax multipliers are highly regime dependent: they are close to zero or statistically insignificant unless taxes are increased when output contracts, fuel prices are high, the environmental tax levels are high, or the carbon intensity of output is low. Commodity trade-exposed countries face higher tax multipliers. This analysis concludes that, compared with income taxes, environmental taxes can be a less contractionary source of revenues to support the post-COVID-19 fiscal consolidation efforts, especially in countries that are at the beginning of their decarbonization efforts.